Ten outcome measures in forensic mental health: A survey of clinician views on comprehensiveness, ease of use and relevance. (9th November 2021) - Ryland, Howard; Cook, Jonathan; Fitzpatrick, Ray; Fazel, Seena
Abstract: Background: Measurement of outcomes in forensic mental health services is essential to ensure that these services are delivering good quality care and treatment. Instruments for outcome measurement should cover all important domains, be easy to implement in a routine clinical context and facilitate transfer of relevant information between clinicians as the patient progresses along a recovery and rehabilitation pathway. Aims: We sought the views of clinicians on 10 common instruments used as outcome measures in forensic mental health services, especially on their perceived comprehensiveness and ease of use. Methods: An online survey was used to gather the views of clinicians from a range of professional backgrounds working in forensic mental health services in the United Kingdom. The selected instruments were identified from a previous systematic review of instruments for measuring outcomes in this context. Questions covered comprehensiveness, ease of use, patient involvement, relevance and use for progressing tracking and care planning. Results: Complete responses were received from 229 individuals. The range of respondents either agreeing or strongly agreeing that individual instruments were comprehensive was 6–39%; easy to use 19%–69%; relevant 31%–78%; useful to measure progress 7–70%; and useful for care planning 33–81%. Respondents reported that, for each of the 10 instruments, full involvement of patients varied between 3% and 22%; partial involvement 12–45%, patients informed, but not involved 11%–28%; and patients not involved or informed 21%‐64%. Conclusions: The Health of the Nation Outcome Scale Secure, the only instrument designed as an outcome measure, is not regarded by clinicians as useful in that respect and the majority of clinicians do not inform patients they are using it. Clinicians appear most familiar with the Historical Clinical Risk 20 (HCR‐20), which some respondents considered potentially useful as a progress measure but with limited patient involvement. Most respondents did not think that the HCR‐20 is comprehensive. There is a need for outcome measures that are comprehensive, easy to use and have adequate patient involvement in their development and rating.